Local resource competition and the skewness of the sex ratio: a demographic model - Lorenzo Mari; Marino Gatto; Renato Casagrandi (Mathematical Biosciences and Engineering)
Most animal populations are characterized by balanced sex ratios, but thereexist several exceptions in which the sex ratio at birth is skewed. Aninteresting hypothesis proposed by Clark (1978) to explain male-biased sexratios is the local resource competition theory: the bias may be expected inthose species in which males disperse more than females, which are thus moreprone to local competition for resources. Here we discuss some of the ideasunderlying Clark's theory using a spatially explicit approach. In particular, wefocus on the role of spatiotemporal heterogeneity as a possible determinant ofbiased sex ratios. We model spatially structured semelparous populations whereeither Ricker density dependence or environmental stochasticity can generateirregular spatiotemporal patterns. The proposed discrete-time model describes bothgenetic and complex population dynamics assuming that (1) sex ratio isgenetically determined, (2) only young males can disperse, and (3) individualslocally compete for resources. The analysis of the model shows that no skewedsex ratios can arise in homogeneous habitats. Temporal asynchronizedfluctuations between two distinct patches coupled with dispersal of young malesis the minimum requirement for obtaining skewed sex ratios of demographic naturein local adult populations. However, the establishment of a male-biased sexratio at birth in the long run is possible if dispersal is geneticallydetermined and there is genetic linkage between sex ratio determination anddispersal.